Analisis Pengaruh Profitabilitas, Likuiditas, Leverage, Tanggung Jawab Sosial Perusahaan terhadap Agresivitas Pajak - Alvin Alvin; Budi Harsono (Global Financial Accounting Journal, 2021)
This research aims to analyze several factors that influence tax aggressiveness in Indonesia. The dependent variable in this research is tax aggressiveness. The independent variables used in this study are profitability, liquidity, leverage, and corporate social responsibility. This study uses secondary data and panel regression analysis methods. The sample data of this study were obtained from the Indonesian Stock Exchange (IDX) as much as 1,285 company data with a period of 5 years from 2015 to 2019. The program used in this research was SPSS version 25 and E-Views Version 10. The results of this study indicate that the leverage variable has a significant positive effect on tax aggressiveness, profitability and the liquidity variable has a significant negative effect on tax aggressiveness. While the result of the corporate social responsibility do not have a significant effect on tax aggressiveness.